Studi Literatur : Meneladani Kisah Nabi Ayyub A.S untuk Kelas VI MI - Ardianti, Siti; Asmalia, Asmalia; Ramadhan, Maratu Naja (Lembaga Yasin AlSys, 2023)
This research is a literature study with a type of descriptive qualitative research with a literature review (library research) that discusses exemplifying the story of Prophet Ayyub (AS). In this literature study research, the author uses various written sources such as articles, journals and documents relevant to the study in this study. This study collected and analyzed a number of literature discussing the story of Prophet Ayyub (AS). sourced from the Quran and Hadith. The results of the study show that the example of Prophet Ayyub can be applied by grade VI MI students. In conclusion, this literature study shows that by emulating the example of Prophet Ayyub students can become individuals who have good morals, and are able to face all life challenges with strength and confidence in God.Keywords: Tafakkur, Syukur, Rahmat